Preparation method of ultra-transparent aerogel sheet material
Through a one-step sol-gel method combined with the drying process, the gel particle size and pore structure are adjusted, and ultra-transparent, elastic and ultra-insulated SiO2 aerogel sheets are prepared, which solves the problem of the lack of ultra-transparency of existing materials and achieves a combination of high transparency and multifunctional performance.
Patent Information
- Application Number
- CN202411440626.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The lack of ultra-transparency of existing SiO2 aerogel materials limits its application scenarios with high transparency requirements, such as cruise ships and architectural glass mezzanines.
Ultra-transparent, elastic and super-insulated aerogel sheets are prepared by combining a one-step sol-gel method with supercritical drying or atmospheric drying processes to regulate the gel particle size and pore structure, and functionalized silicon precursors with alkyl groups on the surface are used to prepare ultra-transparent, elastic and super-insulated aerogel sheets.
It realizes the ultra-transparency of aerogel materials, with a transparency similar to that of glass, with high elasticity and ultra-low thermal conductivity, and is suitable for application scenarios with high transparency requirements, and has the advantages of hydrophobicity and low cost.
Smart Images

Figure CN119612524A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation technology of aerogel porous materials, and relates to a method for preparing an ultra-transparent aerogel sheet. An ultra-transparent, elastic and ultra-insulating multifunctional integrated aerogel sheet is prepared by a simple one-step sol-gel method combined with a supercritical drying or normal pressure drying process. Background Art
[0002] SiO2 aerogel is a porous material composed of a three-dimensional network at the nanoscale. As a gas-solid two-phase material, the solid phase structure provides the conditions for the aerogel block to be formed, so it can be prepared into various shapes of materials; the gas phase is provided by almost 95% of its nanopores, and a large amount of air is covered in the pores. As a poor conductor of heat, air gives the aerogel thermal insulation properties, allowing it to serve in extreme environments. With the rapid development of science and technology, the exploration of various fields has been further developed, and the requirements for the materials used in high-tech equipment have also become more stringent. In the fields of science and technology, chemical industry, etc., equipment is often required to operate in a high-temperature environment, which usually affects the performance and service life of the equipment. This requires a layer of protective device to provide protection and isolate the influence of extreme temperatures to provide a suitable working environment. Zhou (Advanced Materials, 2023, 35(49):10) et al. prepared a layered inorganic silicate aerogel with nanocluster pillars, which achieved synergistic improvements in thermal and mechanical properties. The thermal conductivity of the layered silicate aerogel under air conditions at room temperature (298K) is 0.034W / (m·K), the thermal conductivity under air conditions at high temperature (1073K) is 0.187W / (m·K), and the compressive strength is 80kPa at 42% compression, which provides reliable support for its application. The novel columnar layer structure improves the thermal insulation performance and mechanical stability of the layered inorganic silicate aerogel, opening up a way to explore advanced inorganic aerogels under extreme conditions.
[0003] In addition to thermal insulation properties, mechanical elasticity and transparency have a huge driving force for the widespread application of SiO2 aerogel. Large cargo ships or cruise ships usually travel on the ocean for several days or even months. The scorching sun or cold environment on the ocean makes it difficult for drivers and passengers to bear. Placing highly transparent aerogel in the glass interlayer of the hull can bring its thermal insulation properties into play and provide a comfortable environment inside the ship. In addition, aerogel has mechanical elasticity and can withstand the extrusion of the glass interlayer without breaking. Zhang (Advanced Materials, 2023, 35(29):11) et al. prepared a nanocomposite aerogel with a pearl-like "porous brick and fiber" structure through multi-scale adaptive synthesis and scalable atmospheric pressure drying technology. The thermal conductivity is 0.0174W / (m·K), high tensile and compressive strength (tensile modulus 24MPa and compression modulus 2.2MPa) and high flexural toughness (flexural modulus 8.2·10-6MPa), and it exhibits excellent structural stability under dynamic impact, fatigue stress / strain cycles and extreme temperatures. The aerogel has excellent mechanical and thermal insulation properties and has strong thermal insulation properties under extreme conditions.
[0004] Patent CN202211685237.9 prepared a transparent aerogel with a light transmittance of 80% to 90%. The wet gel needs tedious modification treatment to have hydrophobic properties, and the contact angle is about 106°. The transparency and hydrophobicity of the aerogel are poor, so aerogels with multifunctional integration such as ultra-transparency, elasticity, and ultra-insulation have yet to be developed and applied. Summary of the invention
[0005] The purpose of the present invention is to improve the deficiencies of the prior art and to provide a method for preparing an ultra-transparent aerogel sheet, which is comparable to an ultra-high transparency aerogel sheet of glass, and has the properties of ultra-transparency, elasticity and ultra-insulation. In the past, aerogel materials usually did not have ultra-transparency, and only covered elasticity and insulation functions, and the application scenarios were limited. The material prepared by this patent has the characteristics of ultra-low thermal conductivity, and the ultra-low density makes it more significant compared with most materials of the same volume. The ultra-transparency of this material allows it to be used in the fields of cruise ship glass interlayers, architectural glass interlayers, etc., and it ensures a comfortable temperature inside large machinery and buildings without affecting the light transmittance, and has great application value.
[0006] The technical solution of the present invention is: a method for preparing an ultra-transparent aerogel sheet, and the specific steps are as follows:
[0007] (1) uniformly mixing the acid and the functionalized silicon precursor, stirring at 5 to 60° C. and 200 to 1000 r / min with magnetic stirring for 0.1 to 2 h to obtain a transparent solution;
[0008] (2) adding water and a surfactant to the solution system obtained in step (1), maintaining the same temperature and speed as in step (1) and stirring for 0.1 to 2 hours to obtain a transparent sol system;
[0009] (3) adding the alkaline solution to the sol system obtained in step (2), maintaining the same temperature and speed as in step (1) and stirring for 1 to 60 minutes to obtain a transparent sol;
[0010] (4) pouring the transparent sol obtained in step (3) into a mold and letting it stand for 0.1 to 1 hour to gel, and then aging at 5 to 60° C. for 1 to 12 hours;
[0011] (5) adding the wet gel obtained in step (4) to the replacement fluid for replacement;
[0012] (6) subjecting the wet gel obtained in step (5) to supercritical carbon dioxide drying or atmospheric pressure drying to obtain an ultra-transparent aerogel sheet;
[0013] Wherein: in step (1), the molar ratio of acid to functionalized silicon precursor is (0.001-0.1):1; in step (2), the molar ratio of water, surfactant and functionalized silicon precursor is (1-100):(0.002-0.5):1; in step (3), the molar ratio of alkaline solute in alkaline solution to functionalized silicon precursor is (0.001-1):1.
[0014] Preferably, the acid in step (1) is oxalic acid, acetic acid, hypochlorous acid, hydrochloric acid, sulfuric acid or nitric acid; the concentration of the acid is 0.001 to 1 mol / L.
[0015] Preferably, the functionalized silicon precursor described in step (1) is one or more of methylsilane, methyltrimethoxysilane, methyltriethoxysilane, diethoxymethylsilane, dimethylchlorosilane, vinyltriethoxysilane, phenyltriethoxysilane, 3-aminopropyltriethoxysilane, isobutyltriethoxysilane, n-octyltriethoxysilane or dodecyltrimethoxysilane.
[0016] Preferably, the surfactant described in step (2) is one or more of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, polyether F127, octadecyltrimethylammonium chloride, octadecylmethylpyridinium chloride or polyquaternium-16.
[0017] Preferably, the alkaline solution described in step (3) is one of Na2CO3, NaHCO3, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, ammonia, urea, choline hydroxide or benzyltrimethylammonium hydroxide solution; the concentration of the alkaline solution is 0.01-1 mol / L.
[0018] Preferably, the replacement fluid in step (5) is one or more of water, methanol, ethanol, tert-butyl alcohol, n-hexane, isopropyl alcohol, carbon tetrachloride, toluene or n-decyl alcohol. Preferably, the replacement in step (5) is performed at 30-80° C. for 6-12 times, with an interval of 4-12 hours each time.
[0019] The preferred method of carbon dioxide supercritical drying in step (6) is as follows: carbon dioxide is used as the drying medium, the reaction temperature is 45-50° C., the pressure in the high-pressure reactor is 8-15 MPa, the degassing rate is 2-8 L / min, and the drying time is 4-12 h.
[0020] The preferred method of normal pressure drying in step (6) is to dry the wet gel at three temperatures: 40-60°C, 80-100°C, and 100-120°C, and dry for 2-6 hours at each temperature.
[0021] This patent achieves a synergistic improvement in the ultra-transparency, elasticity and ultra-insulating properties of aerogels through an innovative strategy of regulating the size of gel particles and the size of pore structures. When the functionalized silicon precursor containing alkyl groups on the surface is hydrolyzed, the silicon precursor retains the alkyl groups. After polycondensation, mutually repelling alkyl groups exist on the aerogel skeleton. The existence of repulsive force makes the skeleton structure show excellent elasticity when squeezed. At the same time, the presence of alkyl groups makes the aerogel hydrophobic and can be used in various hot and humid environments without affecting its performance. As a polycondensation catalyst, the alkaline catalyst effectively balances the fiber-like skeleton formed by polysiloxane. This patent prepares ultra-transparent aerogels by controlling the microscopic skeleton characteristics and structural dimensions, and the transparency is almost comparable to that of glass, providing a strategy for the preparation of highly transparent, elastic and highly insulating aerogel sheets.
[0022] Beneficial effects:
[0023] The method of the present invention and the ultra-transparent aerogel sheet prepared by the method have the following characteristics:
[0024] (1) It is technologically innovative. By adjusting the size of gel particles and pore structure at the microscopic level, aerogel has the characteristics of ultra-transparency. The transparency is extremely high, comparable to the transparency of glass, and the visible light transmittance reaches 99%. It also achieves the multifunctional coupling of ultra-transparency, elasticity, and ultra-insulation properties.
[0025] (2) The process route is simple. Through a one-step sol-gel method combined with a supercritical drying process or a normal pressure drying process, an ultra-transparent, elastic, and ultra-insulating aerogel sheet can be obtained. The material has both elasticity and extremely high compressive strength, can withstand a large degree of extrusion, and has rebound properties.
[0026] (3) Low cost. The various reagents used in this patent are all commercially available raw materials. The raw materials are easy to obtain, the materials are efficiently prepared, and the preparation process has low energy consumption, which has the potential for large-scale or industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 1 is a physical picture of the ultra-transparent aerogel sheet prepared in Example 1, wherein (a) is a top view of the ultra-transparent aerogel sheet, and (b) is a side view of the ultra-transparent aerogel sheet;
[0028] Figure 2 1 is a BET test data diagram of the ultra-transparent aerogel sheet prepared in Example 2; wherein (a) is a nitrogen adsorption-desorption curve, and (b) is a pore size distribution curve. DETAILED DESCRIPTION
[0029] Example 1
[0030] Oxalic acid and methylsilane were mixed evenly at a molar ratio of 0.008:1, and stirred at 60°C and 850r / min for 1h to obtain a transparent solution, wherein the concentration of the oxalic acid solution was 1mol / L. Then water and polyquaternium-16 were added to the transparent solution at a molar ratio of 68:0.08:1 of water, polyquaternium-16, and methylsilane, and stirred at the same temperature and speed for 0.5h to obtain a transparent sol system. Choline hydroxide was then added to the sol system at a molar ratio of 1:1 of choline hydroxide and methylsilane, and stirred at the same temperature and speed for 1min to obtain a transparent sol, wherein the concentration of the solute in the choline hydroxide solution was 0.01mol / L. The transparent sol was poured into a mold and allowed to stand for 0.5h to gel, and then aged at 60°C for 5h. The gel was first replaced with a mixed solution of water and methanol at 60°C, where the volume ratio of water to methanol was 1:1. After 8 replacements, it was replaced twice with pure methanol solvent, with an interval of 10 hours each time. The wet gel after methanol replacement was then dried at normal pressure at 40°C, 80°C, and 100°C for 6 hours respectively to obtain an ultra-transparent aerogel sheet. The actual photo of the ultra-transparent aerogel obtained is shown in the figure. Figure 1 As shown, the top view shows that the material has a very high transparency ( Figure 1 (a)), and the aerogel sheet has a thickness of about 7 mm ( Figure 1 (b)), the transmittance is 97%, the specific surface area is 1037m2 / g, 983 compression rebounds are achieved under 50% deformation, the thermal conductivity is 0.023W / (m*K), and the hydrophobic angle is 139°.
[0031] Example 2
[0032] Acetic acid and methyltrimethoxysilane were mixed evenly at a molar ratio of 0.013:1, and stirred at 8°C and 450r / min for 0.25h to obtain a transparent solution, in which the concentration of the acetic acid solution was 0.005mol / L. Then water and polyether F127 were added to the transparent solution at a molar ratio of 5.7:0.002:1 of water, polyether F127, and methyltrimethoxysilane, and stirred at the same temperature and speed for 1.5h to obtain a transparent sol system. Tetramethylammonium hydroxide was then added to the sol system at a molar ratio of 0.039:1 of tetramethylammonium hydroxide and methyltrimethoxysilane, and the same temperature and speed were continued to be stirred for 3min to obtain a transparent sol, in which the concentration of the solute in the tetramethylammonium hydroxide solution was 0.5mol / L. The transparent sol was poured into a mold and allowed to stand for 0.1h before gelling, and then aged at 8°C for 1h. The gel was first replaced with a mixed solution of water and ethanol at 50°C, where the volume ratio of water to ethanol was 1:1. After 6 replacements, it was replaced with pure ethanol solvent twice, with an interval of 12 hours each time. The wet gel after ethanol replacement was then subjected to supercritical carbon dioxide drying, where the reaction temperature was 49°C, the pressure in the autoclave was 10MPa, the degassing rate was 3L / min, and the drying time was 6.5h to obtain an ultra-transparent aerogel sheet. The nitrogen adsorption-desorption curve of the obtained ultra-transparent aerogel ( Figure 2 (a)) and pore size distribution curve ( Figure 2 (b) shows that the material exhibits a typical type IV mixing isotherm, and the maximum pore size distribution is at 23.45 nm ( Figure 2 (b)) proves that the material is a mesoporous material, which is also the reason why it has superinsulation. The material has a transmittance of 99% and a specific surface area of 984m 2 / g, achieved 1002 compression rebounds under 50% deformation, thermal conductivity was 0.018W / (m*K), and hydrophobic angle was 142°.
[0033] Example 3
[0034] Hydrochloric acid and 3-aminopropyltriethoxysilane were mixed evenly at a molar ratio of 0.001:1, and stirred at 5°C and 1000r / min for 0.2h to obtain a transparent solution, wherein the concentration of the hydrochloric acid solution was 0.2mol / L. Then water and hexadecyltrimethylammonium bromide were added to the transparent solution at a molar ratio of 1:0.01:1 of water, hexadecyltrimethylammonium bromide, and 3-aminopropyltriethoxysilane, and stirred at the same temperature and speed for 2h to obtain a transparent sol system. Ammonia water was then added to the sol system at a molar ratio of 0.001:1 of ammonia gas and 3-aminopropyltriethoxysilane, and stirred at the same temperature and speed for 60min to obtain a transparent sol, wherein the concentration of the solute in the ammonia solution was 1mol / L. The transparent sol was poured into a mold and allowed to stand for 0.2h to gel, and then aged at 5°C for 5h. The gel was first replaced with a mixed solution of water and tert-butanol at 80°C, where the volume ratio of water to tert-butanol was 1:1. After four replacements, it was replaced twice with pure tert-butanol solvent, with an interval of 4 hours each time. The wet gel after tert-butanol replacement was then subjected to supercritical carbon dioxide drying, where the reaction temperature was 45°C, the pressure in the autoclave was 15MPa, the degassing rate was 2L / min, and the drying time was 12h to obtain an ultra-transparent aerogel sheet. The ultra-transparent aerogel obtained has a transmittance of 97.6% and a specific surface area of 892m 2 / g, achieved 958 compression rebounds under 50% deformation, thermal conductivity of 0.017W / (m*K), and hydrophobic angle of 146°.
[0035] Example 4
[0036] Hypochlorous acid and dodecyltrimethoxysilane were mixed evenly at a molar ratio of 0.046:1, and stirred at 24°C and 620r / min for 1.3h to obtain a transparent solution, wherein the concentration of the hypochlorous acid solution was 0.06mol / L. Then water and octadecyltrimethylammonium chloride were added to the transparent solution at a molar ratio of 100:0.2:1 of water, octadecyltrimethylammonium chloride, and dodecyltrimethylsilane, and stirred at the same temperature and speed for 0.8h to obtain a transparent sol system. Then NaHCO3 solution was added to the sol system at a molar ratio of 0.72:1 of NaHCO3 and dodecyltrimethylsilane, and stirred at the same temperature and speed for 43min to obtain a transparent sol, wherein the solute concentration in the NaHCO3 solution was 0.08mol / L. The transparent sol was poured into a mold and allowed to stand for 0.8h before gelling, and then aged at 24°C for 9h. The gel was replaced with pure isopropanol solvent at 30°C for 10 times, with an interval of 8 hours each time. The wet gel after isopropanol replacement was then subjected to supercritical carbon dioxide drying, where the reaction temperature was 50°C, the pressure in the autoclave was 8MPa, the degassing rate was 8L / min, and the drying time was 4h to obtain an ultra-transparent aerogel sheet. The ultra-transparent aerogel obtained has a transmittance of 98.5% and a specific surface area of 938m 2 / g, achieved 1021 compression rebounds under 50% deformation, thermal conductivity was 0.020W / (m*K), and hydrophobic angle was 143°.
[0037] Example 5
[0038] Sulfuric acid and isobutyltriethoxysilane were mixed evenly at a molar ratio of 0.1:1, and a transparent solution was obtained after magnetic stirring at 200r / min for 2h at 48°C, wherein the concentration of the sulfuric acid solution was 0.001mol / L. Then water and dodecyldimethylbenzyl ammonium chloride were added to the transparent solution at a molar ratio of water, dodecyldimethylbenzyl ammonium chloride, and isobutyltriethoxysilane of 22:0.5:1, and the transparent sol system was obtained after maintaining the same temperature and speed for 0.1h. Urea was then added to the sol system at a molar ratio of urea to isobutyltriethoxysilane of 0.093:1, and the same temperature and speed were continued to be stirred for 26min to obtain a transparent sol, wherein the solute concentration in the urea solution was 0.8mol / L. The transparent sol was poured into a mold and allowed to stand for 1h before gelling, and then aged at 48°C for 12h. The gel was first replaced with a mixed solution of water and n-hexane at 45°C, where the volume ratio of water to n-hexane was 1:1. After 6 replacements, it was replaced with pure n-hexane solvent 6 times, with an interval of 10 hours each time. The wet gel after n-hexane replacement was then dried at normal pressure at 60°C, 100°C, and 120°C for 2 hours respectively to obtain an ultra-transparent aerogel sheet. The obtained ultra-transparent aerogel was transparent with a transmittance of 98% and a specific surface area of 1012m 2 / g, achieved 926 compression rebounds under 50% deformation, thermal conductivity of 0.023W / (m*K), and hydrophobic angle of 139°.
Claims
1. A method for preparing an ultra-transparent aerogel sheet, the specific steps of which are as follows: (1) uniformly mixing the acid and the functionalized silicon precursor, stirring at 5 to 60° C. and 200 to 1000 r / min with magnetic stirring for 0.1 to 2 h to obtain a transparent solution; (2) adding water and a surfactant to the solution system obtained in step (1), maintaining the same temperature and speed as in step (1) and stirring for 0.1 to 2 hours to obtain a transparent sol system; (3) adding the alkaline solution to the sol system obtained in step (2), maintaining the same temperature and speed as in step (1) and stirring for 1 to 60 minutes to obtain a transparent sol; (4) pouring the transparent sol obtained in step (3) into a mold and letting it stand for 0.1 to 1 hour to gel, and then aging at 5 to 60° C. for 1 to 12 hours; (5) adding the wet gel obtained in step (4) to the replacement fluid for replacement; (6) subjecting the wet gel obtained in step (5) to supercritical carbon dioxide drying or atmospheric pressure drying to obtain an ultra-transparent aerogel sheet; in: The molar ratio of the acid to the functionalized silicon precursor in step (1) is (0.001-0.1):1; the molar ratio of the water, surfactant and the functionalized silicon precursor in step (2) is (1-100):(0.002-0.5):1; and the molar ratio of the alkaline solute in the alkaline solution to the functionalized silicon precursor in step (3) is (0.001-1):
1.
2. The preparation method according to claim 1, characterized in that The acid described in step (1) is oxalic acid, acetic acid, hypochlorous acid, hydrochloric acid, sulfuric acid or nitric acid; the concentration of the acid is 0.001-1 mol / L.
3. The preparation method according to claim 1, characterized in that The functionalized silicon precursor described in step (1) is one or more of methylsilane, methyltrimethoxysilane, methyltriethoxysilane, diethoxymethylsilane, dimethylchlorosilane, vinyltriethoxysilane, phenyltriethoxysilane, 3-aminopropyltriethoxysilane, isobutyltriethoxysilane, n-octyltriethoxysilane or dodecyltrimethoxysilane.
4. The preparation method according to claim 1, characterized in that The surfactant described in step (2) is one or more of dodecyldimethylbenzylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, polyether F127, octadecyltrimethylammonium chloride, octadecylmethylpyridinium chloride or polyquaternium-16.
5. The preparation method according to claim 1, characterized in that The alkaline solution described in step (3) is one of Na2CO3, NaHCO3, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, ammonia, urea, choline hydroxide or benzyltrimethylammonium hydroxide solution; the concentration of the alkaline solution is 0.01-1 mol / L.
6. The preparation method according to claim 1, characterized in that The replacement fluid in step (5) is one or more of water, methanol, ethanol, tert-butanol, n-hexane, isopropanol, carbon tetrachloride, toluene or n-decanol; the replacement is performed at 30-80° C. for 6-12 times, with an interval of 4-12 hours each time.
7. The preparation method according to claim 1, characterized in that The carbon dioxide supercritical drying method described in step (6) is: using carbon dioxide as the drying medium, the reaction temperature is 45-50° C., the pressure in the high-pressure reactor is 8-15 MPa, the degassing rate is 2-8 L / min, and the drying time is 4-12 h.
8. The preparation method according to claim 1, characterized in that The normal pressure drying method described in step (6) is to dry the wet gel at three temperatures: 40-60°C, 80-100°C, and 100-120°C, and dry at each temperature for 2-6 hours.
Citation Information
Patent Citations
A high and low temperature resistant transparent aerogel thermal insulation material with ultraviolet shielding performance and preparation method thereof
CN115893429B
High-strength ultralow-density transparent silicon dioxide aerogel as well as preparation method and application thereof
CN112158852A
Wave-transmitting, efficient and heat-insulating aerogel composite material and preparation method thereof
CN112851292A
Preparation method of super-hydrophobic light transparent high-strength SiO2 aerogel
CN113264532A
Preparation method of hydrophobic high-elastic transparent spherical SiO2 aerogel
CN114408933A